Use of microbial inoculants for production of potato tuber seed in greenhouse conditions - Torres-Vite, H.; Contreras-Liza, S. E. (Peruvian Agricultural Research, 2020)
Objectives: To determine the effect of Glomus intraradices and Bacillus subtilis on the agronomic performance from in vitro potato seedlings in greenhouse conditions. Methodology: The research was developed in pots under greenhouse conditions at Universidad Nacional José Faustino Sánchez Carrión, Huacho, Lima, from October 2017 to March 2018. The substrate for pots was 45% sand, 45% vermicompost, and 10% rice straw, with an average content of 3% organic matter. The average environmental temperature was 25°C. In vitro seedlings of five potato genotypes were transplanted into 4-liter pots, and inoculated with commercial inoculants of Glomus intraradices, a mixture of G. intraradices + Bacillus subtilis, a fertilization treatment with NPK (220-180-120) and control without inoculation. Completely randomized design with four replications on a factorial arrangement was used, with four inoculant treatments and five potato genotypes. The data of ten agronomic characters, that included the weight of the tubers and biomass per plant, were subjected to analysis of variance and then to tests of mean comparison of Scott-Knott and processed with Infostat software. Results: Inoculation treatments with mycorrhizae or mycorrhizae with rhizobacteria, statistically surpassed (P < 0.05) the controls in the case of weight of tubers per plant, the average weight of tubers, number of tubers per plant and diameter of the tuber, in addition to the height of the plant at 15 and days after the transplant; in the case of fresh foliage weight per plant and the degree of senescence of the foliage, the control treatments statistically surpassed (P < 0.05) to the inoculation treatments. For other characters, number of sprouts per plant, the number of leaves and number of flowers per plant, no significant differences (P > 0.05) was found. Conclusions: The use of microbial inoculants based on mycorrhizae and rhizobacteria, improves the productivity of potato seed tubers under greenhouse conditions. Keywords: Glomus intraradices, agronomic performance, in vitro seedlings, potato varieties, greenhouse